Kumari Culture: A Ritualistic and Dialectic Performance - Maharjan, Rubee (Shahid Kirti Multidisciplinary Journal, 2024)
Cultural values and traditions including rites and rituals are the peculiar identities of ethnic groups in Nepal. Newars of Kathmandu valley is one of the indigenous ethnic groups of Nepal with enough prosperity in their unique cultural performances. Every performance in Newari culture, from a typical folklore to native language to the celebration of national Newari festivals, has their own distinguishing features. Among the several aesthetic performances of Newari community is 'Kumari Culture'. In Kathmandu valley, 'Kumari Culture' regards to one of the sacred and idiosyncratic ritual performance where a young girl of age gap between 2-5 belonging to Newar Buddhist community is chosen as the divinity of goddess. The selected 'Kumari', regarded as a living goddess, is then worshipped by entire Nepali citizen. Kumari culture is believed to be originated from ancient Malla reign in the kingdom. Nonetheless, much controversy has arisen regarding Kumari culture in the recent times. Some critics call this culture as a system of child labour whereas, some advocate for the abolishment for its connection to the Royal history. Yet, Kumari culture is a holy form of Newa: Cultural performance that has its own inherent significance. Hence, this paper attempt to examine multi-dimensions of Kumari culture by assessing ritual performances of this culture. Finally, this paper affirms for the recognition of spiritual and dialectical performance of Kumari culture. I would be developing my argument within the fundamental theoretical insights of Richard Schechner and Victor Turner, incorporating the parameters of qualitative analysis.